An open-source platform integrating emerging data sources to support multi-modal active pharmacovigilance - Dimitriadis, Vlasios K.; Dimitsaki, Stella; Chytas, Achilleas; Gavriilidis, George I.; Kakalou, Christine; Bonotis, Panos; Natsiavas, Pantelis (Frontiers in Drug Safety and Regulation, 2023)
As new data sources have emerged, the data space which Pharmacovigilance (PV) processes can use has significantly expanded. However, still, the currently available tools do not widely exploit data sources beyond Spontaneous Report Systems built to collect Individual Case Safety Reports (ICSRs). This article presents an open-source platform enabling the integration of heterogeneous data sources to support the analysis of drug safety related information. Furthermore, the results of a comparative study as part of the project’s pilot phase are also presented. Data sources were integrated in the form of four “workspaces”: (a) Individual Case Safety Reports—obtained from OpenFDA, (b) Real-World Data (RWD) —using the OMOP-CDM data model, (c) social media data—collected via Twitter, and (d) scientific literature—retrieved from PubMed. Data intensive analytics are built for each workspace (e.g., disproportionality analysis metrics are used for OpenFDA data, descriptive statistics for OMOP-CDM data and twitter data streams etc.). Upon these workspaces, the end-user sets up “investigation scenarios” defined by Drug-Event Combinations (DEC). Specialized features like detailed reporting which could be used to support reports for regulatory purposes and also “quick views” are provided to facilitate use where detailed statistics might not be needed and a qualitative overview of the available information might be enough (e.g., clinical environment). The platform’s technical features are presented as Supplementary Material via a walkthrough of an example “investigation scenario”. The presented platform is evaluated via a comparative study against the EVDAS system, conducted by PV professionals. Results from the comparative study, show that there is indeed a need for relevant technical tools and the ability to draw recent data from heterogeneous data sources is appreciated. However, a reluctance by end-users is also outlined as they feel technical improvements and systematic training are required before the potential adoption of the presented software. As a whole, it is concluded that integrating such a platform in real-world setting is far from trivial, requiring significant effort on training and usability aspects.